Recalibration of Political Participation to Restore Democracy and Meritocracy in the 2024 Election - Dwi Putra Nugraha (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The ideas of meritocracy and democracy are seen as running in juxtaposition. Democracy bases results on votes solely without assessing the leader's capabilities. However, meritocracy also creates tyranny in a different form. This is because democracy and meritocracy carry the values of liberalism. This article refutes the conflict between the two concepts and shows the shortcomings of both. Adjustments and improvements to the electoral system and related systems cannot be carried out on a large scale without massive political power. Recalibration of political participation is at least an initial improvement in accordance with the constitutional design of dignified balance to achieve short-term goals. Community political participation in the 2024 elections must be interpreted broadly and substantively. The Voter Participation Index initiated by the KPU has good initial ideas and objectives. However, this paper shows that the method for preparing the IPP needs to be expanded by not only basing the data on applications owned by the KPU alone.